Rancang Bangun Web Pelaporan Dakwah menggunakan Metode Unified Process - Muhammad Ardiansyah; Sirojul Munir (Jurnal Informatika Terpadu, 2022)
Baitul Maal Foundation PLN West Kalimantan Regional Main Unit, as one of the National Amil Zakat Institutions, develops various programs, including da'wah programs. The da'wah program, until now, in providing reports is still manual. The manual system has resulted in several problems, including submitting da'wah reports to the YBM PLN West Kalimantan Regional Main Unit. So we need a da'wah reporting application design to make it easier to submit reports. Building this system is carried out with the stages of data collection, namely literature studies, and interviews. System design and development phases using the Unified Modeling Language diagram modeling and the Unified Process development model. The program's implementation in this application uses the PHP programming language, Laravel Framework, and MySql database. Based on testing the application's functionality using Black Box, the percentage of success is 100%. For the UAT test, the results are 100% on the admin side, 100% on the day side, and 100% on the guest side. Meanwhile, from the results of the questionnaire given to 10 respondents regarding the feasibility of the application, 90% of the results were obtained. It can conclude that the application of the da'wah reporting system makes it easier for the dai to provide reports.